An investigation into the neuroprotective properties of the non-steroidal anti-inflammatory agents tolmetin, sulindac and turmeric - Dairam, Amichand (Rhodes University, Faculty of Pharmacy, Pharmacy, 2006)
Accumulating evidence suggests that anti-inflammatory agents and antioxidants have neuroprotective properties and may be beneficial in the treatment of neurodegenerative disorders. In the present study, the possible neuroprotective properties of tolmetin, sulindac and turmeric were investigated. The antioxidant effects of tolmetin and sulindac were determined by inducing free radical generation with quinolinic acid (QA), cyanide or iron (II) in rat brain homogenates or primary hippocampal neurons. Tolmetin and sulindac significantly reduce lipid peroxidation and scavenge the superoxide anion. Metal binding studies were conducted to determine whether metal chelation is a possible mechanism through which these agents reduce QA and iron (II)-induced lipid peroxidation. UV/VIS, infrared spectroscopy as well as electrochemical studies show that both agents bind to iron (II) and/or iron (III). Histological examination of the hippocampus showed that pre-treatment of animals with tolmetin or sulindac offers protection against intrahippocampal injections of QA. These agents also attenuate QA-induced apoptosis and reduce the loss of neurons in the hippocampus. The co-incubation of primary hippocampal neurons with the NSAIDS also enhanced cell viability which is significantly reduced by QA. Behavioural studies using a water maze showed that the treatment of animals after QA-induced neurotoxicity reduces QA-induced spatial memory loss. Tolmetin and sulindac also reduced glutathione depletion and protein oxidation in rat hippocampus. Both NSAIDS inhibit liver tryptophan 2,3-dioxygenase activity in vitro and in vivo and subsequently increased hippocampal serotonin levels. However, both NSAIDS also reduce dopamine levels in rat striatum. Tolmetin but not sulindac increased the synthesis of melatonin by the pineal gland. The active components of turmeric known as the curcuminoids were separated using preparative thin layer chromatography (TLC). The purity was confirmed by TLC, NMR and mass spectrometry. The environmental toxin lead, induces lipid peroxidation and reduces primary hippocampal neuronal viability. The co-incubation of the neurons with the curcuminoids significantly reduces lead-induced lipid peroxidation and enhances neuronal cell viability in the presence of lead. Lead-induced spatial memory deficit is also attenuated with curcumin, demethoxycurcumin but not bisdemethoxycurcumin. The curcuminoids also reduce lead-induced hippocampal glutathione depletion and protein oxidation. Metal binding studies show that the curcuminoids bind to lead and is another possible mechanism through which the curcuminoids reduce lead-induced neurotoxicity. The findings of this study indicate a possible role of tolmetin, sulindac and turmeric in neurodegenerative disorders such as Alzheimer's disease. However, tolmetin and sulindac reduce dopamine levels.
Keywords: Nonsteroidal anti-inflammatory agents; Antioxidants; Tolmetin -- Therapeutic use; Sulindac -- Therapeutic use; Turmeric -- Therapeutic use; Nervous system -- Degeneration -- Prevention; Alzheimer's disease